Pemberdayaan Masyarakat Melalui Reposisi Masyarakat Dalam Proses Perumusan Penganggaran Di Tingkat Desa (Studi Kasus di Desa Kotayasa dan Banjarsari Wetan, Kecamatan Sumbang, Kabupaten Banyumas) - Sukarso, Sukarso -; Dharma, Swastha -; Dasuki, Niken Paramarti (Universitas Serang Raya, 2019)
So far, policy formulation almost carried out by the elite, even formally the elite has the authority while the community does not. This mechanism conceptualized in the form of formulation models, such as institutional, rational and even incremental models, and especially the elite-mass model. The position of the community directly is generally relatively weak or even almost non-existent. Initiation to involve more community roles in policy formulation has carried out as much as in deliberative and participatory models, but still, the involvement of the community becomes an object, not the subject of policy formulation. This elitist model of policy formulation, especially in Indonesia, occurs both at the national, provincial and district/city levels, the latter at the village level. By these facts, it is interesting to know the potential or prospects of the community, especially at the village level, to be the subject of policy formulation at the village level. This study uses an experimental approach with the treatment of enhancing their understanding and awareness about the formulation of budgeting policies or empowerment in legal, administrative and socio-psychological aspects. This study focuses on the process of formulating village income and expenditure budgets in two villages in Sumbang District, Banyumas Regency. Methods of collecting data using focus group discussions and in-depth interviews with informants selected purposively and questionnaire methods for respondents who chosen accidentally, while analyzing data using interactive. The results of the study show the very high potential and prospects of the community to become an important part and subject to the process of the budgeting policy formulation.